The Effect of Utilization Bentonite and Zeolite in the Broiler Diets on Performance and Fecal Characteristics - Wihandoyo, Wihandoyo; Wahyuni, Tri Hesti; Alimon, AR (ANIMAL PRODUCTION, 2001)
Ninety six commercial strain were conducted from 14 to 42 days of age to evaluate the affect of utilization zeolite and on performance of broiler and fecal characteristics. Birds were divided into four  treatment diets (4 replicates of 7 birds each): K (control), KB (K+ 1% bentonite),  KZ (K+ 1% zeolite), KBZ (K+ 1% Z+ 1% B). The birds were fed initially for two weeks a commercial starter ration and followed by treatment  diets 15 to 42 days of age. All the diets were formulated to have 20% crude protein and 3000 kcal. ME and 0.91% Ca and 0.69% P for control and 0.34% treatments. Body weights and feed intakes were measured on a weekly basis. The manure from each group was sampled on weekly basis and the  moisture content, pH and ammonia production was determined. The results showed the utilization zeolite and bentonite or both significant differences (P<0.05) on pH and (P<0.01) fecal ammonia content, but not on feces water content, final body weight, feed consumption, feed conversion ratio, and carcass. (Animal Production 3(1): 1-4 (2001)